A Worldwide Bibliometric and Visualized Analysis in Publications of Research About Hydrogel in Cartilage Repair - Lai, Jieyu; Yu, Dengjie; Ni, Changkai; Zhang, Aohan; Xiao, Wenfeng; Li, Yusheng (Frontiers in Materials, 2022)
Background: Cartilage defect is a common joint disease. Hydrogels are widely used in the area of cartilage tissue engineering because of their ability to repair the defect cartilage. This study aimed to analyze published research on hydrogels in cartilage repair by using both bibliometric and visualized analysis. Methods: The related articles about hydrogel in cartilage repair was extracted from the Web of Science Core Collection database. SPSS was used for the data analysis. Bibliographic coupling analysis, co-citation analysis, co-authorship analysis and co-occurrence analysis were conducted using VOSviewer. Burst detection conducted with CiteSpace helped to indicate the change of keywords. Results: A total of 1,245 articles related to hydrogels in cartilage repair from 1997 to 2020 were identified and analyzed. Publication numbers grew steadily and reached 187 papers in 2020. The United States contributed the most to the research with the highest number of times cited, average citations and H-index. Over the studied period, Acta Biomaterialia published the most articles about hydrogels in cartilage repair, numbering 77. Johns Hopkins University was the institution that had the highest average citations per item, and Sichuan University, Harvard University, and Kyoto University were tied for the first by the H-index. Ranking first in the world were the National Institutes of Health, specifically the National Institute of Arthritis Musculoskeletal Skin Diseases, the National Institute of Biomedical Imaging and Engineering and the National Institute of Dental Craniofacial Research, which jointly sponsored 383 articles. Conclusions: We provided the research trend of hydrogel in cartilage repair information for global researchers to better understand the facts and future development of research on hydrogels in cartilage repair. The number of publications on hydrogels in cartilage repair will probably still increase in the coming years according to the current trend.